Fungsi Sekretaris dalam Penyelesaian Efisiensi Kerja di Perusahaan - Imhar Imhar; Siti Mutia Fajri (Lembaga Pengembangan Kinerja Dosen, 2022)
This review plans to decide the viability of the secretarial capacity in the organization. Quantitative Spellbinding Exploration. The populace just as the examination test is an irregular number of 15 representatives. Information assortment is taken through perception, polls and documentation. Investigation of the information utilized is unmistakable factual examination, in particular the rate equation. The aftereffects of the review portray the adequacy of the secretarial capacity in accomplishing work proficiency in the organization, seen from different viewpoints, specifically Fruitful or Compelling, Conservative, Responsible Work Execution, Genuine Work Division, Objectivity of Power and obligation, Commonsense work strategies, work and can be carried out, has been executed adequately.